Compatibility Between Communicative Language Teaching (CLT) and Pesantren Learning Values in English Language Learning - Halimah, Mujammilatul; A'la, Bassam Abul (Department of English Language Education, UIN Sunan Ampel Surabaya, 2025)
This study investigates the compatibility between Communicative Language Teaching (CLT) and the traditional learning values embedded within Indonesian pesantren, particularly in the context of English language instruction. While CLT emphasizes communicative competence, learner autonomy, authentic interaction, and meaningful use of language, pesantren education is grounded in values such as discipline, obedience, communal learning, and character formation. These contrasting orientations raise questions about whether CLT can be effectively integrated into pesantren classrooms or whether fundamental pedagogical tensions may arise. Drawing on existing literature on CLT implementation in EFL contexts and studies on pesantren learning culture, this conceptual inquiry examines points of convergence and divergence between the two educational paradigms. Findings indicate several areas of compatibility: both CLT and pesantren prioritize collaborative learning, contextualized meaning-making, and the development of communicative ethics. pesantren traditions such as musya>warah (deliberation) and halaqah (discussion circles) naturally support interactive and cooperative learning, which align with core CLT principles. However, challenges emerge in relation to learner autonomy, teacher, student power relations, and the shift from teacher-centered instruction to student-centered practices. The study argues that with culturally responsive adaptation, such as integrating pesantren-based group practices into communicative activities and reframing autonomy within Islamic educational values, CLT can be harmonized with pesantren learning traditions. Ultimately, the study proposes a hybrid pedagogical model that maintains pesantren identity while enabling communicative English learning, offering implications for curriculum developers, English teachers, and Islamic educational institutions seeking to enhance communicative competence without compromising religious and cultural foundations.